Biomass-Based Silicon and Carbon for Lithium-Ion Battery Anodes - Muraleedharan Pillai, Manoj; Kalidas, Nathiya; Zhao, Xiuyun; Lehto, Vesa-Pekka (Frontiers in Chemistry, 2022)
Lithium-ion batteries (LIBs) are the most preferred energy storage devices today for many high-performance applications. Recently, concerns about global warming and climate change have increased the need and requirements for LIBs used in electric vehicles, and thus more advanced technologies and materials are urgently needed. Among the anode materials under development, silicon (Si) has been considered the most promising anode candidate for the next generation LIBs to replace the widely used graphite. Si cannot be used as such as the electrode of LIB, and thus, carbon is commonly used to realize the applicability of Si in LIBs. Typically, this means forming a-Si/carbon composite (Si/C). One of the main challenges in the industrial development of high-performance LIBs is to exploit low-cost, environmentally benign, sustainable, and renewable chemicals and materials. In this regard, bio-based Si and carbon are favorable to address the challenge assuming that the performance of the LIB anode is not compromised. The present review paper focuses on the development of Si and carbon anodes derived from various types of biogenic sources, particularly from plant-derived biomass resources. An overview of the biomass precursors, process/extraction methods for producing Si and carbon, the critical physicochemical properties influencing the lithium storage in LIBs, and how they affect the electrochemical performance are highlighted. The review paper also discusses the current research challenges and prospects of biomass-derived materials in developing advanced battery materials.